Preparation method and application of oxyhalide solid electrolyte coated graphite
The synthesis of lithium aluminum phosphate solid electrolyte coated graphite through the liquid phase method solves the problem of improving the negative performance of graphite in lithium-ion batteries and the environmental and cost problems of high-temperature solid-phase sintering method, and achieves the improvement of battery performance and process optimization.
Patent Information
- Application Number
- CN202411950097.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The graphite negative electrode performance of existing lithium-ion batteries is close to the theoretical limit, and it is difficult to further improve through traditional methods. Moreover, the preparation of oxyhalide solid electrolytes with high-temperature solid phase sintering method has problems of waste of raw materials, environmental pollution and uneven particle size.
Lithium aluminum phosphate fluoride (LiAlPO4F) solid electrolyte is synthesized by liquid phase method to coat graphite, and the electrochemical performance is improved by generating a dense and uniform LiAlPO4F coating on the surface of the graphite.
The electrochemical performance of graphite negative electrode is improved, the circulation performance and high-temperature performance of lithium-ion batteries are improved, and process costs and energy consumption are reduced.
Smart Images

Figure BDA0005216421520000111 
Figure HDA0005216422570000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a preparation method of oxyhalide solid electrolyte coated graphite and application thereof. Background Art
[0002] Lithium-ion batteries, with their high energy density, fast charge and discharge, and long cycle life, have quickly replaced lead-acid batteries since commercialization and become the main energy storage components in 3C digital products, new energy vehicles, and large energy storage stations. However, with the rapid development of various industries, the performance of lithium-ion batteries under the current technical state is difficult to meet the growing performance requirements. The negative electrode is an important component of lithium-ion batteries, and its performance directly affects the performance of lithium-ion batteries. Currently, the most important negative electrode of lithium-ion batteries is artificial graphite negative electrode. In order to improve the performance of the negative electrode, silicon negative electrode materials, negative electrode etching, and 3D printing technologies have been developed and applied to the battery negative electrode, achieving excellent battery performance. However, these improvements have brought about changes in the lithium-ion battery process. The development of new equipment and changes in production lines have led to a significant increase in production costs, so it is difficult to achieve commercialization in the near future.
[0003] Limited by the structure and physicochemical properties of the graphite negative electrode itself, it is difficult to achieve a significant improvement in rate and capacity. Its own performance is close to the theoretical limit and needs to be improved through modification. Solid electrolyte coating of the negative electrode is a method to improve the performance of the negative electrode. By coating a certain amount of solid electrolyte on the surface of the negative electrode, improving the diffusion of lithium ions in the negative electrode, and affecting the composition of the solid electrolyte interface (SEI) film, a certain gain can be obtained. Moreover, this method is simple in process and can be directly applied to existing production lines, and is expected to be industrialized.
[0004] Generally, adding a coating with high ionic conductivity to the graphite surface can improve the SEI film structure on the negative electrode surface and reduce the interface impedance, thereby improving the rate performance of the graphite negative electrode. Halide solid electrolytes have high ionic conductivity and a wide electrochemical stability window, and have attracted extensive attention from researchers. Among them, the fluorinated phosphate structure has an inductive effect of polyanion PO4 3- The material exhibits a high electrochemical stability window and good structural stability. In particular, lithium aluminum phosphate fluoride (LiAlPO4F), as a fast ion conductor, has excellent Li + Conductivity, is a potential solid electrolyte material. There have been reports on the application of positive electrode, but the application of negative electrode has not yet been involved. Fluorinated lithium aluminum phosphate material is currently mainly prepared by high-temperature solid phase sintering method. The fluorine element is easy to volatilize at high temperature, resulting in waste of raw materials and environmental pollution. At the same time, the grains grow at high temperature, resulting in excessive particle size and uneven distribution, which affects the coating effect and requires complex particle size control process, increasing process cost and energy consumption. Summary of the invention
[0005] In view of this, the present invention provides a method for preparing graphite coated with a halogen oxide solid electrolyte and its application. The method of the present invention can prepare a graphite negative electrode material with better electrochemical performance, thereby improving the use effect in the battery and improving the cycle performance of the lithium ion battery.
[0006] The present invention provides a method for preparing oxyhalide solid electrolyte coated graphite, comprising:
[0007] Step S1, mixing graphite powder, aluminum source, lithium source and phosphorus source, and fluorine-containing buffer in water and reacting them, so that LiAlPO4F generated by the reaction is coated on the graphite surface, and separating to obtain a precursor; the fluorine-containing buffer is a buffer pair composed of ammonium bicarbonate and ammonium fluoride
[0008] Step S2: drying and sintering the precursor in sequence to obtain lithium aluminum phosphate fluoride solid electrolyte coated graphite.
[0009] The embodiment of the present invention mainly proposes a method for synthesizing LiAlPO4F-coated graphite negative electrode by liquid phase method, so as to improve the electrochemical performance of graphite negative electrode and lithium ion battery.
[0010] In the liquid phase synthesis process of the oxyhalide solid electrolyte LiAlPO4F coated graphite described in the embodiment of the present invention, a solution of a water-soluble raw material (including a lithium source, an aluminum source, a phosphorus source, etc.) can be used to react under specific conditions to generate the desired solid electrolyte coated on the graphite surface.
[0011] In some embodiments of the present invention, the graphite powder involved is artificial graphite powder, and the specific particle size D50 is 12-15 μm; the aluminum source is aluminum nitrate or its hydrate; the lithium source is lithium nitrate or its hydrate; the phosphorus source contains phosphate, preferably ammonium phosphate. In addition, a fluorine-containing buffer containing ammonium bicarbonate and ammonium fluoride is used, and water (usually deionized water) is used as a solvent.
[0012] In some embodiments of the present invention, step S1 of the synthesis method or preparation method comprises:
[0013] Step S11, mixing graphite powder, aluminum source, lithium source, fluorine-containing buffer and water to obtain a first solution with a pH value of 9 to 10;
[0014] Mixing a phosphorus source, the fluorine-containing buffer and water to obtain a second solution having a pH value of 9 to 10;
[0015] Step S12: Mix the first solution and the second solution and react them, maintain the pH value at 9-10, so that the LiAlPO4F generated by the reaction is coated on the graphite surface, and separate to obtain a precursor.
[0016] Furthermore, the step S11 includes:
[0017] An aluminum source and a lithium source are added to water to prepare a solution A, graphite powder is dispersed in the solution A, and an aqueous solution of a fluorine-containing buffer is added to obtain a first solution; the pH value of the aqueous solution of the fluorine-containing buffer is 9 to 10;
[0018] A phosphorus source is added into water to prepare solution B, and then the aqueous solution of the fluorine-containing buffer is added to obtain a second solution.
[0019] In step S11 of the embodiment of the present invention, an aluminum source and a lithium source are added to deionized water to prepare a solution, wherein the molar ratio of Li + :Al 3+ =1:1, which is solution A. Artificial graphite powder can be dispersed in the solution A, and stirred sufficiently to make the graphite dispersed evenly.
[0020] Furthermore, a phosphorus source is added to deionized water to prepare a solution, wherein PO4 3- With Li in solution A + The molar ratio is 1:1, which is solution B.
[0021] The fluorine-containing buffer is a buffer pair composed of ammonium bicarbonate and ammonium fluoride, and the reaction is carried out under the condition of pH value of 9 to 10. In the embodiment of the present invention, ammonium bicarbonate and ammonium fluoride can be added to deionized water to prepare an aqueous solution of the fluorine-containing buffer, wherein F - The amount of substance should be the same as the amount of Li in solution A. + The ratio of the amount of the substance is 1:1, and the pH value of the aqueous solution of the fluorine-containing buffer is 9-10; the buffer mainly provides the F required for the synthesis of LiAlPO4F - and the appropriate pH.
[0022] In the embodiment of the present invention, the aqueous solution of the fluorine-containing buffer is added to solutions A and B respectively, so that the pH of the two solutions reaches 9-10, which are respectively recorded as the first solution and the second solution.
[0023] In step S12 described in the embodiment of the present invention, the second solution is gradually added to the first solution, and LiAlPO4F precipitate is generated. During the generation process, a fluorine-containing buffer is continuously added to maintain the pH value at 9 to 10, so that the LiAlPO4F generated by the reaction is coated on the graphite surface. The precipitate can be filtered and repeatedly rinsed with deionized water to obtain a precursor.
[0024] The reactions specifically involved in some embodiments are as follows:
[0025] LiNO3+Al(NO3)3+(NH4)3PO4+NH4F=LiAlPO4F+4NH4NO3.
[0026] After the precursor is obtained, step S2 of the embodiment of the present invention is to dry and sinter it in sequence to obtain a lithium aluminum phosphate fluoride solid electrolyte coated graphite material.
[0027] The embodiment of the present invention is mixed and reacted in a liquid medium, which can avoid the volatilization of fluorine caused by high temperature and the uneven distribution of powder particle size. If the raw material is directly coated on the surface of artificial graphite and then sintered at high temperature to form a coating layer, the high temperature will have a negative impact on the structure of artificial graphite, and the raw material is also easily reduced and decomposed by graphite at high temperature, and it is not easy to form a LiAlPO4F phase; if LiAlPO4F is first sintered at high temperature and then coated on the graphite surface, since high temperature sintering is not conducive to particle size control, complex subsequent processes are required to control the LiAlPO4F particle size, which increases costs.
[0028] In some embodiments of the present invention, the drying in step S2 is performed at 60-120°C for 0.5-12 hours. Further, the drying can be performed in a blast drying oven at 70-110°C for 1-10 hours; the drying temperature can specifically be 80-100°C for 1-8 hours.
[0029] In some embodiments of the present invention, the sintering in step S2 is carried out in an inert atmosphere at a temperature of 300-500° C. for 2-10 hours. Furthermore, the dried powder can be placed in a nitrogen atmosphere and sintered at 300-500° C. for 2-9 hours, preferably sintered for 2-8 hours, to obtain an artificial graphite material coated with LiAlPO4F having a uniform coating layer.
[0030] The embodiment of the present invention mainly uses a liquid phase precipitation method. The particles synthesized by the precipitation method itself have the characteristics of small particle size and concentrated size, which is conducive to forming a dense and uniform coating layer, reducing the direct contact between the graphite negative electrode and the electrolyte, and is conducive to giving full play to the advantages of high conductivity and chemical stability of the coating layer. At the same time, the synthesis process of the present invention is simple, the energy consumption is low, and it is conducive to large-scale promotion and application.
[0031] That is, the embodiment of the present invention prepares a fluorinated lithium aluminum phosphate solid electrolyte coated graphite, which contains a dense and uniform LiAlPO4F solid electrolyte coating layer and has a LiAlPO4F main phase.
[0032] Furthermore, the coating material involved in the embodiment of the present invention is used in a relatively small amount, and the coating amount of the lithium aluminum phosphate fluoride solid electrolyte is preferably 0.1 to 2.5 wt %, and more preferably 0.5 to 2 wt %.
[0033] The present invention provides a negative electrode plate, comprising a conductive agent, a binder and an active material, wherein the active material is lithium aluminum phosphate fluoride solid electrolyte coated graphite obtained by the preparation method described above.
[0034] In some embodiments of the present invention, the content of the active material is above 84 wt %; the conductive agent is conductive carbon black (SP); and the binder is sodium carboxymethyl cellulose (CMC) and / or styrene-butadiene rubber (SBR).
[0035] Further, the negative electrode plate is composed of metal foil (such as copper foil), the above-mentioned coated graphite material, conductive carbon black (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), wherein the coated graphite material accounts for 84.8-94.8wt%, SP accounts for 0-10wt% (can be 0.1-10%), CMC accounts for 0-10wt% (can be 0.1-10%), and SBR accounts for 0-10wt% (can be 0.1-10%). In addition, the present invention has no special restrictions on the preparation method of the negative electrode plate.
[0036] The present invention provides a lithium ion battery, which includes the negative electrode sheet described above. Based on the excellent electrochemical performance of the negative electrode active material described above, its use effect in the battery is improved, thereby improving the cycle performance of the lithium ion battery.
[0037] The lithium-ion battery described in the embodiment of the present invention may be a button-type lithium-ion battery, which comprises a lithium foil, the above-mentioned negative electrode plate, a separator, and an electrolyte. The electrolyte is a conventional electrolyte, such as a carbonate solvent; the separator may be made of polyolefin material, and other components are not particularly limited.
[0038] The main raw materials in the preparation method of the embodiment of the present invention can be lithium nitrate, aluminum nitrate, ammonium phosphate and ammonium fluoride, all of which are water-soluble materials. After being mixed into a solution in a certain proportion, the various element substances are evenly mixed in a liquid phase environment, which is conducive to improving the crystallinity of the product; since the phase generation temperature is low, the volatilization of elements at high temperatures is avoided, and the phase element ratio can be accurately controlled. The present invention uses a fluorine-containing buffer pair as the fluorine source of the solid electrolyte, and at the same time regulates the pH of the solution, avoiding the formation of hydroxide and aluminum ions from ammonia water in a conventional buffer pair to form aluminum hydroxide precipitation, thereby ensuring the precipitation reaction. Its reaction product can be generated in a liquid at room temperature, avoiding uneven growth of grains at high temperatures, and can be evenly coated on the surface of the graphite negative electrode; then the bonding force between the coating layer and the graphite particles is improved by heat treatment, thereby improving the cycle, rate and high temperature performance of the graphite negative electrode and the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the XRD diagram of the powder test obtained in Preparation Example 1 in the embodiment of the present invention. DETAILED DESCRIPTION
[0040] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the drawings and the like in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In order to better illustrate the present invention, the following examples are further illustrated. Unless otherwise specified, the various reagents and raw materials used in the present invention are all commercially available products or products that can be prepared by recognized methods. Unless otherwise specified, the ratios involved are all mass ratios.
[0042] Preparation Example 1:
[0043] This preparation example provides a liquid phase preparation method of a halide oxide solid electrolyte LiAlPO4F coated artificial graphite (coating amount 0.5wt%), and the specific steps are as follows:
[0044] Weigh 0.6896 g (0.01 mol) of lithium nitrate and 2.1300 g (0.01 mol) of aluminum nitrate using a precision balance, add 360 g (20 mol) of deionized water, use a magnetic stirrer to stir at a speed of 300 rpm, and stir for 0.5 hour until the solution is clear and uniform, to obtain solution A; weigh 1.4909 g (0.01 mol) of ammonium phosphate, add 360 g (20 mol) of deionized water, use a magnetic stirrer to stir at a speed of 300 rpm, and stir for 0.5 hour until the solution is clear and uniform, to obtain solution B; weigh 0.3703 g (0.01 mol) of ammonium fluoride, add 360 g (20 mol) of deionized water, use a magnetic stirrer to stir at a speed of 300 rpm, and stir for 0.5 hour until the solution is clear and uniform, add ammonium bicarbonate to adjust the pH of the solution to 9.3, and stir evenly to obtain a buffer solution.
[0045] 296 g of artificial graphite (D50 = 12-15 μm, the same as in the following preparation examples) was added to solution A, and stirred and dispersed using a magnetic stirrer at a speed of 300 rpm for 1 hour to uniformly disperse the graphite particles.
[0046] Use a rubber-tipped dropper to add the fluorine-containing buffer solution to solutions A and B respectively, and adjust the pH to 9.30. Then mix the first solution and the second solution formed, and stir using a magnetic stirrer at a speed of 300 rpm. During the stirring process, the buffer solution is continuously added to maintain the solution pH at 9.30. After the buffer solution is added, stir for another 2 hours.
[0047] After the reaction, the solid particles were filtered with filter paper, rinsed with deionized water several times until the pH of the filtrate was neutral, and dried in an oven at 80°C for 2 hours to obtain a dried powder. The powder was sintered at 300°C for 4 hours under a nitrogen atmosphere, and cooled to obtain LiAlPO4F-coated artificial graphite A (0.5 wt%).
[0048] Preparation Example 2:
[0049] This preparation example provides a liquid phase preparation method of a halide oxide solid electrolyte LiAlPO4F coated artificial graphite (coating amount 0.5wt%), and the specific steps are as follows:
[0050] Weigh 1.2296 g (0.01 mol) of lithium nitrate trihydrate (LiNO3·3H2O) and 3.7500 g (0.01 mol) of aluminum nitrate nonahydrate (Al(NO3)3·9H2O) using a precision balance, add 288 g (16 mol) of deionized water, stir with a magnetic stirrer at a speed of 200 rpm for 1 hour until the solution becomes clear and uniform, and obtain solution A; weigh 1.4909 g (0.01 mol) of ammonium phosphate ((NH4)3PO4), add deionized water 108g (6mol), use a magnetic stirrer to stir at a speed of 200 rpm, stir for 1 hour until the solution is clear and uniform, and obtain solution B; weigh 0.3703g (0.01mol) of ammonium fluoride (NH4F), add 360g (20mol) of deionized water, use a magnetic stirrer to stir at a speed of 400 rpm, stir for 1 hour until the solution is clear and uniform, add ammonium bicarbonate (NH4HCO3) to adjust the solution pH to 9.7, and stir evenly to obtain a fluorine-containing buffer solution.
[0051] 296 g of artificial graphite was added to solution A, and the mixture was stirred and dispersed using a magnetic stirrer at a speed of 300 rpm for 1 hour to uniformly disperse the graphite particles.
[0052] Use a rubber-tipped dropper to add the fluorine-containing buffer solution to solutions A and B respectively, and adjust the pH to 9.50. Then mix the formed first solution and the second solution, and stir with a magnetic stirrer at a speed of 300 rpm. During the stirring process, the buffer solution is continuously added to maintain the solution pH at 9.50. After the buffer solution is added, stir for another hour.
[0053] After the reaction, the solid particles were filtered with filter paper, rinsed with deionized water several times until the pH of the filtrate was neutral, and dried in an oven at 80°C for 2 hours to obtain a dried powder. The powder was sintered at 400°C for 3 hours under a nitrogen atmosphere, and cooled to obtain LiAlPO4F-coated artificial graphite B (0.5 wt%).
[0054] Preparation Example 3:
[0055] This preparation example provides a liquid phase preparation method for oxyhalide solid electrolyte LiAlPO4F coated artificial graphite (coating amount 1wt%), and the difference between its preparation process and Preparation Example 1 is that: 148g of artificial graphite is added to solution A, and a magnetic stirrer is used to stir and disperse at a speed of 300 rpm for 1 hour to make the graphite particles evenly dispersed. The remaining operations are the same to obtain LiAlPO4F coated artificial graphite C (1wt%).
[0056] Preparation Example 4:
[0057] This preparation example provides a liquid phase preparation method of a halogen oxide solid electrolyte LiAlPO4F coated artificial graphite (coating amount 2wt%), and the difference between the preparation process and the preparation example 1 is that: 74g of artificial graphite is added to solution A, and a magnetic stirrer is used to stir and disperse at a speed of 300 rpm for 1 hour to make the graphite particles dispersed evenly. The rest of the operations are the same to obtain LiAlPO4F coated artificial graphite D (2wt%).
[0058] Comparative Preparation Example 1:
[0059] This comparative preparation example provides a method for synthesizing oxyhalide solid electrolyte LiAlPO4F coated artificial graphite by a high temperature solid phase method, comprising:
[0060] Weigh 5.911g (0.08mol) of lithium carbonate (Li2CO3), 12.481g (0.16mol) of aluminum hydroxide (Al(OH)3), 18.404g (0.16mol) of ammonium dihydrogen phosphate (NH4H2PO4), 8.889g (0.24mol, 50% excess) of ammonium fluoride (NH4F) with a precise balance, add 150g of deionized water, grind with a planetary ball mill at a speed of 300 rpm, pour out the solid-liquid mixture after grinding for 2 hours, put it in an oven, and dry it at 80°C for 12 hours to obtain a precursor. Put the precursor into a muffle furnace, sinter it at 700°C for 6 hours at a heating rate of 2°C / min, grind and crush the product after natural cooling to obtain LiAlPO4F prepared by the solid phase method.
[0061] The LiAlPO4F particles were sanded by a nano-sand mill, deionized water was used as the sanding medium, the solid content was 20%, the sanding zirconium balls were 3 mm in diameter, the sanding speed was 2000 rpm, and when the particle size reached the sanding limit, the particles were taken out and dried, and then crushed and depolymerized by a jet mill to obtain nano-LiAlPO4F particles. After depolymerization, the D50 particle size was 738 nm.
[0062] Take 2g LiAlPO4F nanopowder and 200g artificial graphite, add 500g deionized water, stir with a magnetic stirrer at a speed of 400 rpm for 10 hours; then filter the solid particles with filter paper, rinse with deionized water several times until the pH of the filtrate is neutral, dry in an oven at 80°C for 2 hours to obtain a dried powder. Sinter at 400°C for 3 hours under a nitrogen atmosphere, and obtain LiAlPO4F-coated artificial graphite E (1wt%) after cooling.
[0063] In addition, a synthesis example of lithium aluminum fluoride phosphate liquid phase powder is provided to verify the phase purity of the material prepared by the precipitation method. The preparation process of the liquid phase powder synthesis example is as follows:
[0064] Weigh 6.896 g (0.1 mol) of lithium nitrate (LiNO3) and 21.300 g (0.1 mol) of aluminum nitrate (Al(NO3)3) on a precision balance, add 90 g (5 mol) of deionized water, stir with a magnetic stirrer at a speed of 300 rpm for 0.5 hour until the solution is clear and uniform, and obtain solution A; weigh 14.909 g (0.1 mol) of ammonium phosphate ((NH4)3PO4), add 90 g (5 mol) of deionized water ), using a magnetic stirrer to stir at a speed of 300 rpm, stirring for 0.5 hour until the solution is clear and uniform, to obtain solution B; weighing 3.703 g (0.1 mol) of ammonium fluoride (NH4F) and adding 90 g (5 mol) of deionized water, using a magnetic stirrer to stir at a speed of 300 rpm, stirring for 0.5 hour until the solution is clear and uniform, adding ammonium bicarbonate (NH4HCO3) to adjust the solution pH to 9.3, stirring evenly to obtain a fluorine-containing buffer solution.
[0065] Use a rubber-tipped dropper to add the fluorine-containing buffer solution to solutions A and B respectively, and adjust the pH to 9.30. Then mix solution A and solution B, and stir them using a magnetic stirrer at a speed of 300 rpm. At this time, a white precipitate is generated. During the formation of the precipitate, the buffer solution is continuously added to maintain the solution pH at 9.30.
[0066] After the reaction is completed, filter paper is used for filtration, and deionized water is used for filtration for multiple times until the pH value of the filtrate is neutral. The precipitate is taken out and dried in an oven at 80° C. for 2 hours to obtain LiAlPO4F powder.
[0067] The powders obtained in the above liquid phase powder synthesis example and comparative preparation example 1 were tested by X-ray diffraction (XRD), and the results are as follows Figure 1 shown.
[0068] After being crushed by jet mill, the powder was passed through a 200-mesh sieve. The sieved powder was prepared into a 10% solid aqueous solution with deionized water. The particle size was analyzed using a laser particle size analyzer. The obtained particle size data are shown in Table 1.
[0069] Table 1 Particle size analysis results
[0070] Powder Chemical formula D10(nm) D50(nm) D90(nm) Liquid phase powder synthesis example <![CDATA[LiAlPO4F]]> 352 533 807 Comparative Preparation Example 1 <![CDATA[LiAlPO4F]]> 237 738 3248
[0071] Depend on Figure 1 It can be seen that both synthesis methods can obtain the main phase of LiAlPO4F, and there is a small amount of AlPO4 second phase. Compared with the high-temperature solid phase method, the peak intensity of the second phase synthesized by the liquid phase method is lower, indicating that the purity of the main phase is higher. As can be seen from Table 1, the particle size of the halogen oxide solid electrolyte particles prepared by the liquid phase method is significantly smaller than that of the high-temperature solid phase method, and the particle size distribution is narrower. Since the synthesis temperature of the liquid phase method is relatively low, the elements are evenly distributed in the solvent, and grain growth will not occur due to high temperature after nucleation. The nucleation particle size is relatively uniform, so solid electrolyte particles with high crystallinity and small particle size can be obtained, which is conducive to achieving a uniform and dense coating layer.
[0072] Battery application test
[0073] 1. Preparation of negative electrode and button battery
[0074] Example 1
[0075] The negative electrode slurry composition ratio is as follows: 94.8wt% LiAlPO4F coated with artificial graphite A (0.5wt%), 1wt% SP, 1.7wt% CMC, 2.5wt% SBR, coated on copper foil using a 100μm scraper, and placed in an oven after coating and drying at 180°C for 12 hours. After drying, it is rolled and cut into negative electrode sheets with a diameter of 12mm.
[0076] The button cell uses the negative electrode prepared above, the lithium sheet is used as the reference electrode, and the electrolyte is LiPF6 / EC-DEC-5% FEC, where LiPF6, EC, DEC and FEC represent lithium hexafluorophosphate, ethylene carbonate, diethyl carbonate and fluoroethylene carbonate, respectively. The electrolyte is prepared by dissolving 1M LiPF6 in an EC / DEC system with a volume ratio of 1:1 and adding 5wt% FEC; the separator uses a polyethylene (PE) battery separator. The assembly steps are as follows:
[0077] Step 1: Place the negative electrode shell flat on an insulating table, place the lithium sheet in the center of the negative electrode shell, and use a tablet pressing mold to flatten the lithium sheet. Then place the diaphragm flat on the upper layer of the lithium sheet, and use a pipette to take an appropriate amount of electrolyte droplets and add them to the surface of the diaphragm.
[0078] Step 2: Use insulating tweezers to place the negative electrode plate, gasket, spring sheet and positive electrode shell on the upper layer of the diaphragm in sequence, with the active material side of the negative electrode plate close to the diaphragm.
[0079] Step 3: Use insulating tweezers to place the button battery with the negative electrode side facing up on the button battery sealing machine mold. You can use a paper towel to pad the top of the battery to absorb the overflowed electrolyte. Adjust the pressure (usually 800Pa) and press for 5s to complete the assembly and preparation of the button battery. Take it out with insulating tweezers, observe whether the preparation appearance is complete and wipe it clean with a paper towel to obtain button battery A.
[0080] Example 2
[0081] The difference between this embodiment and embodiment 1 is that the negative electrode particles used are LiAlPO4F-coated artificial graphite B (0.5 wt %) obtained in preparation example 2, and the other operations remain the same to obtain button battery B.
[0082] Example 3
[0083] The difference between this embodiment and embodiment 1 is that the negative electrode particles used are LiAlPO4F-coated artificial graphite C (1 wt %) obtained in preparation example 3, and the other operations remain the same to obtain a button battery C.
[0084] Example 4
[0085] The difference between this embodiment and embodiment 1 is that the negative electrode particles used are LiAlPO4F-coated artificial graphite D (2 wt %) obtained in preparation example 4, and the other operations remain the same to obtain a button battery D.
[0086] Comparative Example 1
[0087] The difference between this comparative example and Example 1 is that the negative electrode particles used are LiAlPO4F-coated artificial graphite E (1 wt %) obtained in Comparative Preparation Example 1, and the other operations remain the same to obtain button battery E.
[0088] Comparative Example 2
[0089] The difference between this comparative example and Example 1 is that the negative electrode particles used are uncoated artificial graphite negative electrode particles, and the other operations remain the same to obtain a button battery F.
[0090] 2. Battery performance test
[0091] Examples 1 to 5 and comparative examples 1 to 2 were subjected to room temperature (25°C) and high temperature (60°C) cycle tests, and the test procedure was as follows: 0.1C constant current discharge to 0.01V, 0.02C constant current discharge to 0.01V, 0.01C constant current discharge to 0.01V, after 1 minute of standing, 0.01C constant current charge to 2V, and standing for 1 minute.
[0092] The test results are shown in Table 2. The test was repeated for 200 cycles at room temperature and 100 cycles at high temperature.
[0093] Table 2 Battery performance results of the present invention examples
[0094]
[0095] As can be seen from the table, oxyhalide solid electrolytes as negative electrode additives can improve the room temperature and high temperature cycle performance of the battery. This may be because the F element in the electrolyte participates in the formation of the SEI film on the surface of the negative electrode active material, making the SEI film more stable; at the same time, the solid electrolyte has high ionic conductivity and is distributed on the surface of the negative electrode active material, which improves the Li ion transmission path and is also beneficial to improving the battery's cycle performance. Compared with the LiAlPO4F obtained by the high-temperature solid phase method, the coating layer LiAlPO4F prepared by the liquid phase method has a smaller particle size and a narrower particle size distribution, making the coating layer more dense and uniform, and the improvement effect is better.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing graphite coated with an oxyhalide solid electrolyte, characterized in that: include: Step S1, mixing graphite powder, aluminum source, lithium source and phosphorus source, and a fluorine-containing buffer in water and reacting them, so that LiAlPO4F generated by the reaction is coated on the graphite surface, and separating to obtain a precursor; the fluorine-containing buffer is a buffer pair composed of ammonium bicarbonate and ammonium fluoride; Step S2: drying and sintering the precursor in sequence to obtain lithium aluminum phosphate fluoride solid electrolyte coated graphite.
2. The preparation method according to claim 1, characterized in that: The graphite powder is artificial graphite powder; the aluminum source is aluminum nitrate or aluminum nitrate hydrate; the lithium source is lithium nitrate or lithium nitrate hydrate; and the phosphorus source is ammonium phosphate.
3. The preparation method according to claim 1, characterized in that: The preparation method comprises: Step S11, mixing graphite powder, aluminum source, lithium source, fluorine-containing buffer and water to obtain a first solution with a pH value of 9 to 10; Mixing a phosphorus source, the fluorine-containing buffer and water to obtain a second solution having a pH value of 9 to 10; Step S12: Mix the first solution and the second solution and react them, maintain the pH value at 9-10, so that the LiAlPO4F generated by the reaction is coated on the graphite surface, and separate to obtain a precursor.
4. The preparation method according to claim 3, characterized in that: The step S11 comprises: An aluminum source and a lithium source are added to water to prepare a solution A, graphite powder is dispersed in the solution A, and an aqueous solution of a fluorine-containing buffer is added to obtain a first solution; the pH value of the aqueous solution of the fluorine-containing buffer is 9 to 10; A phosphorus source is added into water to prepare solution B, and then the aqueous solution of the fluorine-containing buffer is added to obtain a second solution.
5. The preparation method according to claim 4, characterized in that: In step S2, the drying is performed at 60 to 120° C. for 0.5 to 12 hours.
6. The preparation method according to claim 5, characterized in that: In the step S2, the sintering is performed in an inert atmosphere at a temperature of 300 to 500°C for a time of 2 to 10 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In the lithium aluminum phosphate fluoride solid electrolyte coated graphite, the coating amount of the lithium aluminum phosphate fluoride solid electrolyte is 0.1-2.5wt%.
8. A negative electrode sheet, comprising a conductive agent, a binder and an active material, characterized in that: The active material is lithium aluminum phosphate fluoride solid electrolyte coated graphite obtained by the preparation method according to any one of claims 1 to 7.
9. The negative electrode sheet according to claim 8, characterized in that: The content of the active material is above 84wt%; the conductive agent is conductive carbon black; and the binder is sodium carboxymethyl cellulose and / or styrene-butadiene rubber.
10. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as described in claim 8 or 9.